2019
DOI: 10.1002/mc.23140
|View full text |Cite
|
Sign up to set email alerts
|

Gartanin is a novel NEDDylation inhibitor for induction of Skp2 degradation, FBXW2 expression, and autophagy

Abstract: Gartanin, a 4-prenylated xanthone, has been identified from the purple mangosteen fruit as a potent growth inhibitor of various cancer cell lines, including prostate cancer. However, much of Gartanin's anti-cancer mechanism remains unknown. We have discovered that Gartanin docked onto the regulatory subunit of the precursor cell-expressed developmentally down-regulated 8 (NEDD8)-activating enzyme (NAE) complex and next to the NEDD8 binding complex, which leads to inhibit NEDD8 conjugations to both Cullin1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…In this cell line, the activation of autophagy, which also regulated cell cycle arrest, was the mechanism that mediated the anti-proliferative effects of gartanin [320]. Similarly, it was demonstrated that gartanin (6-24 µM) inhibited the growth of prostate cancer cells (22Rv1, PC-3) by triggering autophagy, as shown by the increase in LC3 II punctuate staining and the increase in LC3 II expression [321].…”
Section: Xanthonesmentioning
confidence: 74%
See 1 more Smart Citation
“…In this cell line, the activation of autophagy, which also regulated cell cycle arrest, was the mechanism that mediated the anti-proliferative effects of gartanin [320]. Similarly, it was demonstrated that gartanin (6-24 µM) inhibited the growth of prostate cancer cells (22Rv1, PC-3) by triggering autophagy, as shown by the increase in LC3 II punctuate staining and the increase in LC3 II expression [321].…”
Section: Xanthonesmentioning
confidence: 74%
“…However, the use of autophagy inhibitors showed the enhancement of gartanin-induced apoptotic cell death [318]. Conversely, different studies reported the induction of autophagy, as a cell death mechanism, mediated by gartanin [319][320][321]. Liu et al demonstrated that gartanin (10-25 µM) induced both apoptosis and autophagy through the inhibition of the mTOR pathway in urinary bladder cancer cells (T24 and RT4) [319].…”
Section: Xanthonesmentioning
confidence: 99%
“…With inhibition of the neddylation of Cullin1 and Ubc12, flavokawain A (FKA), flavokawain B (FKB), and gartanin induced Skp2 degradation, which inhibited cell growth and induced autophagy in prostate cancer [ 121 , 122 , 123 ]. All-trans retinoic acid (ATRA) induces ubiquitylation and degradation of the F-box protein Skp2 in Cullin1 independent manner.…”
Section: Inhibitors Targeting Skp2 Overcome Resistancementioning
confidence: 99%
“…A γ-secretase inhibitor, DAPT, selectively depleted CD133 + cells, suppressed activated NOTCH1 and Skp2, induced p27, inhibited ACC growth in vivo, and sensitized CD133 + cells to radiation [ 65 ]. Gartanin docked onto the NEDD8-activating enzyme (NAE) complex, which results in inhibition of neddylation while inducing proteasomal-dependent Skp2 degradation [ 123 ].…”
Section: Inhibitors Targeting Skp2 Overcome Resistancementioning
confidence: 99%
See 1 more Smart Citation